2022
DOI: 10.1149/2162-8777/ac4edb
|View full text |Cite
|
Sign up to set email alerts
|

Review—Biowaste as a Source of Conductive Carbon

Abstract: Recycling trends have transformed the prerequisites of our cravings making the recycling of waste material into useful goods inevitable. Bio waste is a major portion of waste materials, and as such must be pursued for recycling. Activated carbon from bio waste has been shown to have remarkable electrochemical performance. This survey of data has been compiled for different bio wastes as a source of activated carbons with conductive behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…141 The literature reported that biowastes have variable mean C content: nearly 35% for cereal straws, sugarcane bagasse, pitch, lower for seaweed (16%) and approximately 50 wt% for fruit shells. 142 A comprehensive study on various bio-based sources for conductive carbon has been recently made by Zia et al , 143 including agricultural crops, energy crops, crop residue, forest, forestry residue, aquatic crops, municipal waste and industrial waste, confirming the high potential application of these materials in sectors for energy storage and harvesting. Elemental composition in terms of nitrogen content also confirmed values of 1–5% in agricultural 144 and food wastes.…”
Section: Biowaste Feedstocks For Nanofillersmentioning
confidence: 97%
“…141 The literature reported that biowastes have variable mean C content: nearly 35% for cereal straws, sugarcane bagasse, pitch, lower for seaweed (16%) and approximately 50 wt% for fruit shells. 142 A comprehensive study on various bio-based sources for conductive carbon has been recently made by Zia et al , 143 including agricultural crops, energy crops, crop residue, forest, forestry residue, aquatic crops, municipal waste and industrial waste, confirming the high potential application of these materials in sectors for energy storage and harvesting. Elemental composition in terms of nitrogen content also confirmed values of 1–5% in agricultural 144 and food wastes.…”
Section: Biowaste Feedstocks For Nanofillersmentioning
confidence: 97%
“…Adsorption on carbonaceous materials is well known approach 27 , 28 . Adsorption of heavy metals on biowaste derived carbonaceous matter is thought to be more cost-effective than commercial activated carbon, most probably owing to the conductive nature 29 . As a byproduct of widespread industrialization, large quantities of carbonaceous wastes are produced from the processing of many carbon-based materials.…”
Section: Introductionmentioning
confidence: 99%